165k views
4 votes
The explicit formula for the geometric sequence -1/9,1/3,-1,3,-9

User Stasi
by
5.3k points

1 Answer

5 votes
ANSWER



\boxed {a_n= - (1)/(9) {( - 3)}^(n - 1) }


Step-by-step explanation

The given geometric sequence is



- (1)/(9) , (1)/(3) , - 1,3, - 9,...


The first term of the geometric sequence is,


a_1= - (1)/(9)

and there is a common ratio of


r = ( (1)/(3) )/( - (1)/(9) ) = - 3


The explicit formula, for the geometric sequence is given by,



a_n=a_1 {r}^(n - 1)



We substitute the values into the formula to get the explicit formula as,



a_n= - (1)/(9) {( - 3)}^(n - 1)
User Nidal
by
5.3k points